Reimagining Urban Public Spaces Through Digital Art : A Framework For Cultural Engagement And Inclusive City- Making In Hangzhou, China - Liu, Dan; Salmiah, Abdul Hamid (Academic Science Publications and Distributions, 2025)
Integration of digital technologies in public art installations has a significant potential for the transformation of urban spaces, however many of such initiatives have failed in leaving a lasting impact. Absence of a uniform design framework for connecting the intents of the artist with the technological execution, becomes one of the key challenges. The present study endeavors to fill the identified gap with the introduction to a seven-phase design framework for guiding the execution, public value as well as the sustainability of digital art within public sphere. The study uses the case study method under the qualitative research strategy in Hangzhou, China, to conduct semi-structured interviews with digital artists and representatives from technology enterprises. The research utilizes the NVivo analytical tool for analyzing the interview data, forming the structured framework that includes Requirements Analysis, Design Conceptualization, Technical Implementation, User Experience Testing, Optimization, Implementation and Maintenance, and Post-Installation Evaluation. The framework foregrounds the vitality of interdisciplinary collaboration, technology adaptability and user-centred design. The framework shall provide practical suggestions encouraging cultural engagement, promoting inclusive form of community participation, along with encouraging social innovation and sustainability at the economic level. The findings contribute towards the policy strategies of urban culture of incorporating digital art into urban development, aligning artistic creativity with technological strength. This study offers important insights for policymakers and practitioners with the aim for harnessing digital public art for cultural revitalization and sustainable urban innovation.